Cytokine Signature Associated With Disease Severity in COVID-19 - Guo, Jing; Wang, Shuting; Xia, He; Shi, Ding; Chen, Yu; Zheng, Shufa; Chen, Yanfei; Gao, Hainv; Guo, Feifei; Ji, Zhongkang; Huang, Chenjie; Luo, Rui; et al. (Frontiers in Immunology, 2021)
Coronavirus disease 2019 (COVID-19) broke out and then became a global epidemic at the end of 2019. With the increasing number of deaths, early identification of disease severity and progression is very important. Aiming to identify biomarkers for disease severity and progression of COVID-19, 81 COVID-19 patients, 34 healthy controls and 23 patients with influenza A (H1N1) were recruited for this study. Using liquid chip technology, 48 cytokines and chemokines were examined, among which 33 were significantly elevated in COVID-19 patients compared with healthy controls. Compared with the H1N1 group, 30 cytokines were significantly increased in the COVID-19 group. Compared with mild cases, 16 cytokines were significantly elevated in severe cases, including IP-10, M-CSF, MIG and SCGF-β. G-CSF, HGF, IL-1ra, IL-6 and 9 in critical cases, including IP-10, M-CSF, SCF, HGF, and IL-1ra. IP-10, SCF, HGF, IL-1ra and IL-10 correlated positively with virus titres. Moreover SCGF-β was negatively associated with the lymphocyte count. IP-10 and M-CSF were excellent predictors for the progression of COVID-19, with the best sensitivity and specificity, respectively. In conclusion, these data indicate that hypercytokinaemia appears in the early stage of severe cases, and serum cytokines may be used as early warning indicators of the severity and progression of COVID-19. Early stratification of disease and intervention to reduce hypercytokinaemia may improve the prognosis of COVID-19 patients.